Crystal structure of the extracellular domain of the receptor-like kinase TMK3 from Arabidopsis thaliana - Chen, Hong (International Union of Crystallography, 2020)

(untitled) (Acta Crystallogr F Struct Biol Commun)
Transmembrane kinases (TMKs) are members of the plant receptor-like kinase (RLK) family. TMKs are characterized by an extracellular leucine-rich-repeat (LRR) domain, a single transmembrane region and a cytoplasmic kinase domain. TMKs have been shown to act as critical modulators of cell expansion and cell proliferation. Here, the crystal structure of the extracellular domain of TMK3 (TMK3-ECD) was determined to a resolution of 2.06 Å, with an R (work) of 17.69% and an R (free) of 20.58%. Similar to the extracellular domain of TMK1, the TMK3-ECD structure contains two solenoids with 13 LRRs and a non-LRR region (316–364) between the tenth and 11th LRRs. A comparison of TMK3-ECD with other LRR-RLKs that contain a non-LRR region indicates that the non-LRR region plays a critical role in structural integrity and may contribute to ligand interactions. The non-LRR region of TMK3-ECD is characterized by two disulfide bonds that may have critical biological implications.